The concept of professionalism in media from the journalists’ perspective in Jordan - Tahat, Khalaf Mohammad; Khalaf Lafee Alhammad, Zuhair Yaseen Tahat,; Qublan, Bashar Mahmoud (Opción, 2020)
The study aimed at identifying the level of awareness of Jordanian journalists and social media activists of the professionalism concept in the media. This study was based on the survey method, which is an organized approach in obtaining information, data, phenomenon descriptions. As a result, there is a statistically significant difference in the awareness of Jordanian journalists and activists of social networking sites of how each group perceives their nature role towards their society in what they publish. In conclusion, journalists are more likely to violate ethical practices in journalism for the public good than activists.